A CRITICAL ANALYSIS OF ENGLISH FOR ULAMA PROGRAM: A COLLABORATION BETWEEN WEST JAVA LOCAL GOVERNMENT AND BRITISH COUNCIL INDONESIA - Istianah Ramadani (Magister Ilmu Administrasi Publik, 2020)
Indonesia is a country with the largest Muslim population in the world, with Java having the biggest number of Muslim scholars (ulamas), in Indonesia. Nonetheless, it is unfortunate that participation of Indonesian ulamas in international da’wa or sermon is very limited. One of the obstacles Ulamas face in proselytizing in foreign countries is the weak English language proficiency. English is today has become the most freqeuntly used international language in the 21st century, making it a lingua franca, and a valuable means of international communication. This articles assesses a program that involved the collaboration between West Java provincial government and the British Council Indonesia to provide English training for Ulamas in West Java. The program was tailored toward enhancing English proficiency of Ulamas, which in turn was expected to their ability to participate in proselytization activities and dialogues abroad. The objective of this research was to assess the evolution of the program to become the policy of West Java provincial governor, as well as the conduct, progress and performance of the program. Motivation to learn and the leanrning community were some of the key factors that influnced the performance of the English for Ulama program.However, limited time and budget were some of the key obstacles that contrained program performance. Conclusions were used to draw several policy recommendations.